Instrument to Assess the Perception of Sound and Rhythm for Children with Hearing Impairment - Hernawati, Tati; Rusyani, Endang; Wibowo, Setyo Wahju; Herawati, Nenden Ineu (Department of Special Education, 2023)
Children with hearing impairments experience hearing loss from mild to profound, which is grouped into hard of hearing and deafness. The direct impact of hearing loss is the inability/difficulty to catch various sounds, including the sound of the language. Those with hearing impairments must be made aware of sound, especially children classified as hard of hearing, whose remaining hearing must be stimulated to train their sensitivity so that their hearing function can be optimized. Therefore, they are given special services in the form Development of Communication, Perception of Sound and Rhythm. The program provided must be under their learning conditions and needs; therefore, an assessment is needed. This study aimed to formulate an assessment instrument for sound and rhythm perception for children with hearing impairments at Special Education Elementary School. This study used a qualitative approach with a descriptive method. This study was designed in three stages: (1) preliminary stage with literature study and documentation study on the curriculum for developing sound and rhythm perception communication,f (2) drafting stage of the assessment instrument for Sound and Rhythm Perception, and (3) validation stage of assessment instrument by measurement & education experts for children with hearing impairment and practitioners (teachers at Special Education School). The result was a hypothetical sound and rhythm perception assessment instrument that needed to be implemented at the next research stage. This instrument for assessing the perception of sound and rhythm covered the aspects of sound detection, sound discrimination, and sound comprehension. This study result can be used as a reference for teachers in carrying out a sound perception assessment before conducting a special program for Developing Communication for the Perception of Sound and Rhythm.